Cadherin-11 Is a Regulator of Intestinal Fibrosis. (23rd September 2019) - Franzè, Eleonora; Monteleone, Ivan; Laudisi, Federica; Rizzo, Angelamaria; Dinallo, Vincenzo; Di Fusco, Davide; Colantoni, Alfredo; Ortenzi, Angela; Giuffrida, Paolo; Di Carlo, Sara; Sica, Giuseppe S; Di Sabatino, Antonio; et al.
Abstract: Background and Aims: Although the mechanisms underlying the formation of intestinal fibrostrictures in Crohn's disease [CD] are not fully understood, activation of fibroblasts and excessive collagen deposition are supposed to contribute to the development of such complications. Here, we investigated the role of cadherin-11 [CDH-11], a fibroblast-derived protein that induces collagen production in various organs, in intestinal fibrosis. Methods: CDH-11 expression was evaluated in inflammatory [I] and fibrostricturing [FS] CD mucosal samples, ulcerative colitis [UC] mucosal samples, and ileal and colonic control samples, by real-time polymerase chain reaction, western blotting, and immunohistochemistry. CDH-11 expression was evaluated in normal and in CD intestinal fibroblasts stimulated with inflammatory/fibrogenic cytokines. FS CD fibroblasts were cultured either with a specific CDH-11 antisense oligonucleotide [AS], or activating CDH-11 fusion protein and activation of RhoA/ROCK, and TGF-β pathways and collagen production were evaluated by western blotting. Finally, we assessed the susceptibility of CDH-11-knockout [KO] mice to colitis-induced intestinal fibrosis. Results: CDH-11 RNA and protein expression were increased in both CD and UC as compared with controls. In CD, the greater expression of CDH-11 was seen in FS samples. Stimulation of fibroblasts with TNF-α, interleukin [IL]-6, IFN-γ, IL-13, and IL-1β enhanced CDH-11 expression. Knockdown of CDH-11 in FS CD fibroblasts impaired RhoA/ROCK/TGF-β signalling and reduced collagen synthesis, whereas activation of CDH-11 increased collagen secretion. CDH-11 KO mice were largely protected from intestinal fibrosis. Conclusions: Data show that CDH-11 expression is up-regulated in inflammatory bowel disease [IBD] and suggest a role for this protein in the control of intestinal fibrosis.